Factors influencing the growth of financial services in Jamaica - McBain, Helen ([Caribbean Centre for Money & Finance] [St. Augustine]TT, 1996)
Focuses on facros influencing the growth of financial services. Examines the relationship between financial services and economic growth as a factor affecting the translation of financial resources into productive growth.